2007
DOI: 10.1111/j.1365-2222.2007.02788.x
|View full text |Cite
|
Sign up to set email alerts
|

Exhaled nitric oxide and biomarkers in exhaled breath condensate indicate the presence, severity and control of childhood asthma

Abstract: Different markers in condensate are of an additional value to exhaled nitric oxide, and are needed in non-invasive inflammometry. They could be useful to diagnose asthma and to indicate asthma control and severity in childhood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
84
3
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(93 citation statements)
references
References 38 publications
3
84
3
3
Order By: Relevance
“…EBC lyophilisation can concentrate samples up to a factor of 30 times, thus improving sensitivity [ 61 ]. There was no relationship between EBC cytokine concentrations and storage times up to 1 year in samples stored at − 80 ° C [ 157 ]. With newer technologies, EBC cytokine measurement may become useful in assessing airway inflammatory status for treatment monitoring and investigating disease pathophysiology [ 156 ].…”
Section: Cytokines Chemokines and Growth Factorsmentioning
confidence: 99%
“…EBC lyophilisation can concentrate samples up to a factor of 30 times, thus improving sensitivity [ 61 ]. There was no relationship between EBC cytokine concentrations and storage times up to 1 year in samples stored at − 80 ° C [ 157 ]. With newer technologies, EBC cytokine measurement may become useful in assessing airway inflammatory status for treatment monitoring and investigating disease pathophysiology [ 156 ].…”
Section: Cytokines Chemokines and Growth Factorsmentioning
confidence: 99%
“…FeNO levels did not significantly differ in women before and after they lost asthma control. 84 In a prospective study that followed patients who were mostly on ICS (age 10 and over) for 12 weeks, FeNO did not correlate with ACQ or with shortened ACQ (without FEV 1 ). 86 In terms of the use of FeNO to predict asthma exacerbations, several studies showed higher FeNO values in patients who had had exacerbations prior to the test (retrospective analysis) or had developed exacerbations after the test (prospective analysis).…”
Section: Kq1b Risk Of Bias Assessment Of Observational Studiesmentioning
confidence: 99%
“…The ability to non-invasively characterize airway tissue by repeated measurements of biomarkers in EBC would be invaluable for studying the time-course of dynamic inflammatory pathways that are involved in asthma exacerbation. Ultimately, EBC biomarkers may contribute to the assessment of different asthma phenotypes and the development of individualized rational approaches to asthma management at the point of care [6][7][8][9] .…”
Section: Introductionmentioning
confidence: 99%